Analisis Makna Majas Metonimia pada Manga Suzume No Tojimari - Nita Nurhasti; Retno Utari (Jurnal Bahasa Jepang Taiyou, 2025)
This study aims to analyze the meaning of metonymy in the manga Suzume no Tojimari. This manga was chosen because it contains a lot of dialog that is in accordance with the metonymic style that reflects the social, cultural, and emotional background of the characters. The purpose of this study is to indetify the meaning and function of metonymic majas used by the characters in the manga.This research uses descriptive method with qualitative approach. The technique used in data collection is content analysis. The results show that the use of metonymic figures of speech in this manga does nos only function as languase decoration, but also plays an important role in building characters, conveying emotions, and reinforcing the Japanese cultural context.